2010
DOI: 10.1186/1471-2164-11-94
|View full text |Cite
|
Sign up to set email alerts
|

Development of a EST dataset and characterization of EST-SSRs in a traditional Chinese medicinal plant, Epimedium sagittatum (Sieb. Et Zucc.) Maxim

Abstract: BackgroundEpimedium sagittatum (Sieb. Et Zucc.) Maxim, a traditional Chinese medicinal plant species, has been used extensively as genuine medicinal materials. Certain Epimedium species are endangered due to commercial overexploition, while sustainable application studies, conservation genetics, systematics, and marker-assisted selection (MAS) of Epimedium is less-studied due to the lack of molecular markers. Here, we report a set of expressed sequence tags (ESTs) and simple sequence repeats (SSRs) identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
138
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 48 publications
24
138
2
3
Order By: Relevance
“…pigeonpea (Wang et al, 2010;Dutta et al, 2011). Interestingly, the CCG/CGG and CG/CG motifs have the lowest dominant repeat type in N. nucifera, which is consistent with the results from dicotyledonous plants (Kumpatla and Mukhopadhyay 2005), such as Epimedium sagittatum (Jiang et al, 2012) and radish (Zeng et al, 2010;Jiang et al, 2012). These results showed that the CCG/ CGG motif is the rarest motif in a large number of dicotyledonous plants.…”
Section: Frequency and Distribution Of Different Types Of Genic-ssrs supporting
confidence: 79%
See 2 more Smart Citations
“…pigeonpea (Wang et al, 2010;Dutta et al, 2011). Interestingly, the CCG/CGG and CG/CG motifs have the lowest dominant repeat type in N. nucifera, which is consistent with the results from dicotyledonous plants (Kumpatla and Mukhopadhyay 2005), such as Epimedium sagittatum (Jiang et al, 2012) and radish (Zeng et al, 2010;Jiang et al, 2012). These results showed that the CCG/ CGG motif is the rarest motif in a large number of dicotyledonous plants.…”
Section: Frequency and Distribution Of Different Types Of Genic-ssrs supporting
confidence: 79%
“…About 9% (9523 contigs) of the transcriptomic sequences possessed SSR loci. This rate was higher than for Epimedium sagittatum (3.67%), which were identified using the same search parameters (Zeng et al, 2010). The distribution density in N. nucifera is one microsatellite loci per 6.84 kb.…”
Section: Frequency and Distribution Of Different Types Of Genic-ssrs mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, EST-SSRs have a relatively high transferability compared with genomic SSRs (Wei et al, 2011b). With the development of next-generation sequencing technologies, many EST-SSRs have been found and evaluated in sweet potato (Wang et al, 2010), chickpea (Garg et al, 2011), Epimedium sagittatum (Zeng et al, 2010), Siberian wildrye (Zhou et al, 2016), and multiple other species. However, the results of these studies have shown that SSRs vary in different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…These SSR markers can be isolated from both conserved coding regions and non-coding nucleotide sequences of all higher organisms (Sraphet et al, 2011). The development of genomic SSRs, however, is relatively timeconsuming and expensive; but SSRs can alternatively be found in public sequence databases of expressed sequence tags (ESTs) or cDNA (Zeng et al, 2010;Huang et al, 2011;Sraphet et al, 2011;Koelling et al, 2012). Such SSRs are referred to as EST-SSRs.…”
Section: Introductionmentioning
confidence: 99%